Kendala yang Dihadapi Guru dan Orang Tua dalam Pembelajaran Tahfidz Siswa Masa Pandemi Covid-19 - Jayanti, Suci; Septiana, Mira; Prananosa, Ahmad Gawdy; Adisel, Adisel (JOEAI (Journal of Education and Instruction), 2022)
This study aims to describe the obstacles faced by teachers and parents in assisting children to memorize the Qur'an. The research method used is a descriptive qualitative approach. The sample consists of 6 people consisting of 1 teacher and 5 guardians of students, taken using a random technique. Data obtained by means of observation, interviews, and documentation, analyzed by data reduction taking into account the validity of the data, methods and triangulation. The results of this study indicate that the obstacles experienced by teachers and parents in carrying out Tahfidz Al-Qur'an learning for grade IIIA students at SDIT Al-Yasiir Bengkulu City during the pandemic are the short duration of time studying at school so teachers must think about methods and media in learning children from home online, the use of technology related to Android cellphones, not all parents can operate the cellphone so that teachers find it difficult to provide information to students, parents who are busy working, and parents who cannot read the Qur'an. In conclusion, the obstacles faced by teachers and parents are communication tools, time and the ability of teachers and parents to provide direction and guidance to children in learning Tahfidz Al-Qur'an students at SDIT Al-Yasiir Bengkulu City. Keywords: Teacher, parent, Pandemic Covid-19